Holographic interferometer for controlling transparent substrates of diffractive optical elements - Avlasevich, Nataliya T.; Buts, Andrey I.; Lialikau, Aliaksandr M. (Journal of the Belarusian State University. Physics, 2017)
The procedures of optical manufacturing inspection necessitate implementation of relatively simple and effective interference devices enabling realization of various methods to control optical elements. This paper presents a scheme of holographic optical interferometer suitable for the working conditions; the interferometer may be used for the interference quality control of optical elements such as a phase diffraction grating on the transparent glass substrate. The suggested procedure is based on comparison between the element controlled and the reference. In the interferometer scheme under consideration the final interferogram is formed by superposition of two light beams (object and reference) with a spatial shift comparable to the diameter of the beam itself and exceeding the linear dimensions of the diffractive optical element (DOE) under study. The resultant interference patterns for the substrates of DOEs subjected to the control procedures are given. The proposed method may be used for the optical manufacturing inspection of DOEs.